HISTORICAL INSIGHTS ON SRIMANTA SANKARDEVA AND THE NEO-VAISHNAVISM MOVEMENT: SOCIO-POLITICAL AND CULTURAL TRANSFORMATIONS IN MEDIEVAL ASSAM - Pathak, Guptajit; Palit, Projit Kumar (International Journal of Research -GRANTHAALAYAH, 2023)
The Neo-Vaishnavism (Eka-Sarana Nama Dharma) movement, which was founded by Srimanta Sankardeva (1449–1568 C.E.), is credited with changing the religious, social, and cultural paths of medieval Assam. Through inclusive institutions like Namghars, Sattras, and Bhaona performances, Sankardeva’s reformist mission aimed to integrate disparate ethnic communities and spread devotion (bhakti) based on a single, accessible divine principle in the face of caste stratification, communal tensions, and fragmented politics.1 His movement left lasting effects on identity formation and intercommunal cohesion over the ensuing decades, influencing the Assamese language, arts, social conventions, and political affiliations. The research conducts a critical historical analysis of the Neo-Vaishnavite movement in Assam, examining its dual roles as a socio-cultural revolution and a religious reform. In addition to examining how his disciples institutionalized his vision, it places Sankardeva’s activities within the political framework of Ahom, Koch, and Baro-Bhuyan power dynamics and evaluates the resulting changes in caste attitudes, gender norms, ritual practices, and literary culture. The study unearths the continuities and disturbances his movement created by combining original chronicles (like Buranjis), hagiographical sources, and existing scholarship. The study contends that Neo-Vaishnavism was a powerful social engineering tool in medieval Assam rather than just a religious doctrine, and that despite changes, its influence can still be seen in Assamese society today.